Comparison of the effects of major fatty acids present in the Mediterranean diet (oleic acid, docosahexaenoic acid) and in hydrogenated oils (elaidic acid) on 7-ketocholesterol-induced oxiapoptophagy in microglial BV-2 cells. (October 2017) - Debbabi, Meryam; Zarrouk, Amira; Bezine, Maryem; Meddeb, Wiem; Nury, Thomas; Badreddine, Asmaa; Karym, El Mostafa; Sghaier, Randa; Bretillon, Lionel; Guyot, Stéphane; Samadi, Mohammad; Cherkaoui-Malki, Mustapha; et al.
Highlights: Oleic acid is the major fatty acid of olive and dietary argan oil. 7-Ketocholesterol induces oxiapoptophagy on BV-2 murine microglial cells. Oleic and docosahexaenoic acid impair 7-ketocholesterol-induced oxiapotophagy. Elaidic acid (trans-isomer of oleic acid) also attenuates 7-ketocholesterol-induced oxiapotophagy. Only oleic acid, but not elaidic acid, was able to impair 7-ketocholesterol-induced increase of plasma membrane fluidity. Abstract: Increased levels of 7-ketocholesterol (7KC), which results mainly from cholesterol auto-oxidation, are often found in the plasma and/or cerebrospinal fluid of patients with neurodegenerative diseases and might contribute to activation of microglial cells involved in neurodegeneration. As major cellular dysfunctions are induced by 7KC, it is important to identify molecules able to impair its side effects. Since consumption of olive and argan oils, and fish is important in the Mediterranean diet, the aim of the study was to determine the ability of oleic acid (OA), a major compound of olive and argan oil, and docosahexaenoic acid (DHA) present in fatty fishes, such as sardines, to attenuate 7KC-induced cytotoxic effects. Since elaidic acid (EA), the trans isomer of OA, can be found in hydrogenated cooking oils and fried foods, its effects on 7KC-induced cytotoxicity were also determined. In murine microglial BV-2 cells, 7KC induces cell growth inhibition, mitochondrial dysfunctions, reactive oxygen species overproduction and lipid peroxidation, increased plasma membrane permeability and fluidity, nuclei condensation and/or fragmentation and caspase-3 activation, which are apoptotic characteristics, and an increased LC3-II/LC3-I ratio, which is a criterion of autophagy. 7KC is therefore a potent inducer of oxiapoptophagy (OXIdation + APOPTOsis + autoPHAGY) on BV-2 cells. OA and EA, but not DHA, also favor the accumulation of lipid droplets revealed with Masson's trichrome, Oil Red O, and Nile Red staining. The cytotoxicity of 7KC was strongly attenuated by OA and DHA. Protective effects were also observed with EA. However, 7KC-induced caspase-3 activation was less attenuated with EA. Different effects of OA and EA on autophagy were also observed. In addition, EA (but not OA) increased plasma membrane fluidity, and only OA (but not EA) was able to prevent the 7KC-induced increase in plasma membrane fluidity. Thus, in BV-2 microglial cells, the principal fatty acids of the Mediterranean diet (OA, DHA) were able to attenuate the major toxic effects of 7KC, thus reinforcing the interest of natural compounds present in the Mediterranean diet to prevent the development of neurodegenerative diseases.